In vitro and in vivo comparison of transport media for detecting nasopharyngeal carriage of Streptococcus pneumoniae - Anneke Steens; Natacha Milhano; Ingeborg S. Aaberge; Didrik F. Vestrheim (PeerJ, 2016)
Background As a standard method for pneumococcal carriage studies, the World Health Organization recommends nasopharyngeal swabs be transported and stored at cool temperatures in a medium containing skim-milk, tryptone, glucose and glycerol (STGG). An enrichment broth used for transport at room temperature in three carriage studies performed in Norway may have a higher sensitivity than STGG. We therefore compared the media in vitro and in vivo. Methods For the in vitro component, three strains (serotype 4, 19F and 3) were suspended in STGG and enrichment broth. Recovery was compared using latex agglutination, quantification of bacterial loads by real-time PCR of the lytA gene, and counting colonies from incubated plates. For the in vivo comparison, paired swabs were obtained from 100 children and transported in STGG at cool temperatures or in enrichment broth at room temperature. Carriage was identified by latex agglutination and confirmed by Quellung reaction. Results In vitro, the cycle threshold values obtained by PCR did not differ between the two media (p = 0.853) and no clear difference in colony counts was apparent after incubation (p = 0.593). In vivo, pneumococci were recovered in 46% of swabs transported in STGG and 51% of those transported in enrichment broth (Kappa statistic 0.90, p = 0.063). Discussion Overall, no statistical differences in sensitivity were found between STGG and enrichment broth. Nevertheless, some serotype differences were observed and STGG appeared slightly less sensitive than enrichment broth for detection of nasopharyngeal carriage of pneumococci by culturing. We recommend the continued use of STGG for transport and storage of nasopharyngeal swabs in pneumococcal carriage studies for the benefit of comparability between studies and settings, including more resource-limited settings.